Aged garlic extract as a potential prophylactic to reduce the progression of endometriosis and associated pain burden - Redwood, Emily; Lam, Virginie; Takechi, Ryusuke; Kerr, Deborah Anne; Jackaman, Connie; Sharif, Arazu; Mamo, John Charles Louis (Frontiers in Pain Research, 2022)
Endometriosis is a complex and potentially debilitating condition that has major impact on quality of life. There is emerging evidence that biological compounds found in garlic (Allium sativum) may be effective for attenuating endometrial pain. Suggested mechanisms for efficacy include modulation of inflammation and potent antioxidant effects. Aged-garlic-extract (AGE) is a centuries old process describing ethanolic extracts of garlic bulbs for 12–20 months. The AGE formulation realised contains a complex array of stabilised biologics with significant immunomodulatory effects relevant to inflammatory conditions. This perspective article puts forward a hypothesis that AGE should be considered as a prophylactic to manage endometrial pain.